2021
DOI: 10.33961/jecst.2021.00017
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Improvement of Vanadium Redox Flow Battery by Integrating Electrode and Bipolar Plate

Abstract: An integral electrode-bipolar plate assembly, which is composed of electrode, conductive adhesive film (CAF) and bipolar plate, has been developed and evaluated for application with a vanadium redox flow battery (VRB) to decrease contact resistance between electrode and bipolar plate. The CAF, made of EVA (ethylene-vinyl-acetate) material with carbon black or CNT (Carbon Nano Tube), is applied between the electrode and the bipolar plate to enable an integral assembly by adhesion. In order to evaluate the integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Y Liu et al 24 achieved higher efficiency and better cycling stability at a wide temperature range by reducing the ratio of vanadium ion concentration to proton concentration. Min et al 25 integrated graphite electrodes with bipolar plates in their research and found that it can enhance the EE of batteries. They investigated changes in battery voltage efficiency (VE) and coulomb efficiency (CE) by studying contact resistance.…”
mentioning
confidence: 99%
“…Y Liu et al 24 achieved higher efficiency and better cycling stability at a wide temperature range by reducing the ratio of vanadium ion concentration to proton concentration. Min et al 25 integrated graphite electrodes with bipolar plates in their research and found that it can enhance the EE of batteries. They investigated changes in battery voltage efficiency (VE) and coulomb efficiency (CE) by studying contact resistance.…”
mentioning
confidence: 99%